Uncatalyzed Synthesis of New Antibacterial Bisarylidene Meldrum's Acid Derivatives Functionalized with Ether Groups - Moosazadeh, Elham; Sheikhhosseini, Enayatollah; Ghazanfari, Dadkhoda; Soltaninejad, Shahla (Letters in Organic Chemistry, 2019)
A series of new bisarylidene Meldrum’s acid derivatives (3a-i) were prepared in high yield by a condensation reaction between Meldrum's acid and ether functionalized dibenzaldehyde, without any catalyst. Regardless of the nature of the substitution, all the reactions were completed within 2-3 hours in ethanol at reflux condition. In the reactions, the column purification of the products was not needed. The FT-IR, 1H-NMR, 13C-NMR and mass spectra confirm the structure of the products. Furthermore, the antibacterial activities of some synthesized compounds were investigated. According to the results, these compounds showed good activities against Staphylococcus aureus, Bacillus cereus, E. coli and Pseudomonas aeruginosa.
Keywords: biological activity media